Preparation, characterization and stability of KF/Si-MCM-41 basic catalysts for application in soybean oil transesterification with methanol. Issue 2 (June 2015) - Ranucci, C.R.; Colpini, L.M.S.; Monteiro, M.R.; Kothe, V.; Gasparrini, L.J.; Alves, H.J.
Graphical abstract: Highlights: Were developed novel catalysts from Si-MCM-41 by treatment with KF. The treatment resulted in the formation of new crystalline phases. Test of activity in the methanolysis of soybean oil for the synthesis of biodiesel. Were reached conversion rates of 99.9% in reaction conditions considered mild. Were obtained basic catalysts with stability superior to that of [CTA + ]Si-MCM-41. Abstract: New solid catalysts with basic properties were obtained by treating Si-MCM-41 mesoporous molecular sieves with KF. The following characterization techniques were used in this study: XRD, SEM, TGA and BET. The experimental results indicated that the KF/Si-MCM-41 catalysts possess basic active sites dispersed on the surface, which generate basicity equivalent to that of [CTA + ]Si-MCM-41. In general, the newly developed catalysts showed stability superior to that of [CTA + ]Si-MCM-41 in leaching tests, as well as high catalytic activity in the transesterification reaction of soybean oil with methanol for the production of alkyl monoesters. The maximum rate of conversion into alkyl monoesters was 99.9% in 1 h of reaction at 343 K, using 5 wt.% of catalyst, and a molar ratio of oil to alcohol of 1:12.